Concerning Personality Tests and Human Resource Performance: Wataseuake.com Analysis System Literature Review - Dwi Kusuma, Dyah Ayu; Sopiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The potential of personality tests to enhance HR management and worker output has attracted a lot of interest. The Wataseuake.com Analysis System is a novel approach to assessing employees' personalities that makes use of adaptive testing processes, cutting-edge algorithms, and real-time data analytics. Integrating AI and ML allows us to evaluate the system's reliability and validity in comparison to widely used personality tests while also addressing privacy and ethics concerns. The research also discusses the constraints and future advancements in human resource management, as well as the long-term effects of using the Wataseuake.com Analysis System in different types of organizations. Future enhancements and customization options for the system are also addressed. This study adds to the ongoing discussion on how to enhance modern human resource practices by synthesizing existing research, calling attention to knowledge gaps, and discussing the real-world implications of this innovative strategy. The results imply that improving our knowledge of employee characteristics may improve recruiting, teamwork, and output. modern human resource practices by integrating previous research, highlighting gaps in knowledge, and providing insights into the practical consequences of this new approach. In this article, we will look at how personality testing has affected employment performance. It looks at the validity, reliability, and ethical concerns of these tests from a psychometric perspective. The findings of the research imply that a better grasp of employee personalities might boost recruitment efforts, collaboration, and productivity. Insights from the review help plan future studies.